Best proximity point theorems for cyclic p-contractions with some consequences and applications - Aslantas, Mustafa; Sahin, Hakan; Altun, Ishak (Nonlinear Analysis: Modelling and Control, 2021)
In this paper, we introduce the concept of cyclic p-contraction pair for single-valued mappings. Then we present some best proximity point results for such mappings defined on proximally complete pair of subsets of a metric space. Also, we provide some illustrative examples that compared our results with some earliest. Finally, by taking into account a fixed point consequence of our main result we give an existence and uniqueness result for a common solution of a system of second order boundary value problems.
Keywords: best proximity point; cyclic p-contractions; fixed point; boundary value problem